2013
DOI: 10.1371/currents.outbreaks.2193a0ec4401d9526203af12e5024ddc
|View full text |Cite
|
Sign up to set email alerts
|

The Dry Season in Haiti: a Window of Opportunity to Eliminate Cholera

Abstract: Background: Since the beginning of the cholera epidemic in Haiti, attack rates have varied drastically with alternating peak and lull phases, which were partly associated with the fluctuating dry, rainy and cyclonic seasons. According to a study conducted in 2012, the toxigenic V. cholerae O1 strain responsible for the outbreak did not settle at a significant level in the Haitian aquatic environment. Therefore, we hypothesize that some areas of lingering cholera transmission during the dry season could play an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…21 This may support findings by Dowell et al 22 showing increased incidence of pneumococcal disease during times of seasonal change in the US. Predominance of respiratory tract infections during the rainy season has been reported in tropical climates, 23,24 and high rates of pneumonia deaths among children were also reported in Kenya during the rainy season.…”
Section: Discussionsupporting
confidence: 79%
“…21 This may support findings by Dowell et al 22 showing increased incidence of pneumococcal disease during times of seasonal change in the US. Predominance of respiratory tract infections during the rainy season has been reported in tropical climates, 23,24 and high rates of pneumonia deaths among children were also reported in Kenya during the rainy season.…”
Section: Discussionsupporting
confidence: 79%
“…Diarrhea in adults is also likely to be reported as cholera independently of its actual origins because laboratory confirmation could not be performed for every single patient due to the huge number of cases. Rebaudet et al (2013) estimated a background noise of diarrhea cases not related to cholera of about 250 cases per week. This noise source is not relevant when analyzing outbreak peaks, but it may become important during lull phases.…”
Section: Discussionmentioning
confidence: 99%
“…However, local exposure/contamination rates could also have changed over the timescales considered in this study (as proposed in [8], where it was suggested that transmission patterns may have changed significantly in time and space). A first plausible mechanism to explain this change is the increasing awareness of the population about the mechanisms of cholera transmission, as a result of the campaigns for hygiene promotion set-up by Haitian authorities and non-governmental organizations [49,51]. Increased knowledge about cholera and its transmission dynamics may have prompted behavioural changes in the population at risk of infection, thus significantly influencing cholera dynamics [52].…”
Section: Discussionmentioning
confidence: 99%